Melodies of Doves, Clamor from the Towers: The Dawn of Granada’s Sonic Conversion - Stamper, Aaron (The sixteenth century journal, 2022)
Following the 1492 conquest of Granada, the Catholic Monarchs (r. 1474-1516) introduced a series of edicts aimed at converting the majority-Muslim community. Without much success during the first years, Queen Isabel and King Ferdinand approved the forced conversion of the entire city and surrounding region in 1499. From that moment until the final expulsion of the Moriscos (converted Muslims) from 1609 to 1614, Castilian authorities attempted to regulate their activities to ensure against heresy and political treason. Granada, however, remained a multicultural space in which the melodies of zambra music, meandering Catholic processions, and Islamic prayers resounded through homes and streets alike. This article explores Granada’s historical soundscape and Castilian auditory strategies of reform and conversion. It shows how the struggle for religious and cultural rights was carried out in the sonic realm and argues for a wider reading of sensorial experience in the past.